2023
DOI: 10.3390/microorganisms11030626
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Biomarkers of Active Pulmonary TB Course

Abstract: The spread of drug-resistant forms of TB dictates the need for surgical treatment in the complex of anti-tuberculosis measures in Russia. Most often, surgical intervention is performed in the case of pulmonary tuberculoma or fibrotic cavitary tuberculosis (FCT). This study is devoted to the search for biomarkers that characterize the course of disease in surgical TB patients. It is assumed that such biomarkers will help the surgeon decide on the timing of the planned operation. A number of serum microRNAs, pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…mir-103a-3p was selected based on previous research, which demonstrated its superior statistical performance compared to the commonly used reference RNAs in miRNA qRT-PCR experiments involving human samples. The data analysis revealed a standard deviation of Cq: 4.06, with a mean of 30.2 and a median of 29.4 [ 9 , 10 ]. The CFX96 Touch Real-time PCR Detection System (Bio-Rad, CA, USA) was used to conduct RT-qPCR.…”
Section: Methodsmentioning
confidence: 99%
“…mir-103a-3p was selected based on previous research, which demonstrated its superior statistical performance compared to the commonly used reference RNAs in miRNA qRT-PCR experiments involving human samples. The data analysis revealed a standard deviation of Cq: 4.06, with a mean of 30.2 and a median of 29.4 [ 9 , 10 ]. The CFX96 Touch Real-time PCR Detection System (Bio-Rad, CA, USA) was used to conduct RT-qPCR.…”
Section: Methodsmentioning
confidence: 99%
“…M.tb possesses many virulent factors that interact with host cells and interfere with the host’s immune responses. However, the ways in which M.tb survives in the hostile environment of the human organism is still a subject of investigation [ 46 , 47 , 106 ]. The interplay between M.tb virulence factors and the host are in a constant battle whose outcome will determine whether the TB symptoms will manifest or whether the bacterium will be removed [ 107 ].…”
Section: Challenges In Tb Vaccine Research and Innovations—the Tip Of...mentioning
confidence: 99%
“…The interplay between M.tb virulence factors and the host are in a constant battle whose outcome will determine whether the TB symptoms will manifest or whether the bacterium will be removed [ 107 ]. The identification of distinct immunological parameters would be good indicators for the performance of the vaccine pre, during or post-vaccination [ 106 , 107 , 108 ]. Knowledge of immune markers or the expression of M.tb virulence factors inside the host will give us a clear picture of the workings of the human organism during infection, vaccination, latency, and follow-up period [ 109 ], so that the treatment plan can be adjusted accordingly to provide maximum protection against TB.…”
Section: Challenges In Tb Vaccine Research and Innovations—the Tip Of...mentioning
confidence: 99%
“…Indeed, direct comparison of miRNA expression patterns between the tuberculoma group and the post-COVID-19 tuberculoma group showed that only a few miRNA genes were similarly expressed in these groups (Figure 5c). Further analysis of miRNA expression in the serum of TB patients by qRT-PCR using a set of markers that previously allowed us to reliably estimate the activity of specific inflammation in patients with tuberculoma [20] gave the following results, as presented in Figure 6. The levels of miRNA expression in the serum of healthy subjects, patients with tuberculosis without a history of COVID-19, and patients co-infected with tuberculosis and COVID-19 were evaluated.…”
Section: Serum Mirna Expression Pattern Of Tb Patients 3 Months Post-...mentioning
confidence: 99%
“…Recently, we published the results of our investigation on serum miRNAs as biomarkers of the TB course in surgical patients [20]. Based on these results, here, we used a panel of TB-associated miRNAs to characterize TB activity in surgical patients with pulmonary tuberculoma as well as in surgical patients with pulmonary tuberculoma and a history of COVID-19.…”
Section: Introductionmentioning
confidence: 99%